Development of a population dynamics model to investigate the displacement of Rhipicephalus decoloratus by Rhipicephalus microplus - Fosgate, Geoffrey Theodore (University of Pretoria, 2023)
Mini Dissertation (MSc (Veterinary Epidemiology))--University of Pretoria, 2022.